Group identification as a mediator of the effect of players’ anonymity on cheating in online games - Chen, Vivian Hsueh-Hua (2015)
This study aims to add to the discussion about the applicability of the classical deindividuation theory and social identity model of deindividuation effects (SIDE) in explaining online behaviours. It explores the effect of anonymity in facilitating social influence of group identity in online game cheating. A nationally representative survey was conducted face to face. Results from the survey administered in Singapore confirm predictions derived from the SIDE and challenge the classical deindividuation theory. Specifically, it was concluded that the frequency of gaming with online strangers (anonymous gaming) significantly predicted the frequency of cheating in online games. The effect of anonymity on game cheating was found to be significantly mediated by the group identification with online gaming communities/groups. Gender differences were found. Male gamers cheated more frequently than female gamers. Female gamers are more likely to cheat as a consequence of group identification than male gamers. Implications and future research are discussed.